The effect of varying dietary protein and antibiotic levels on the performance of weanling local pigs - ILORI , J.O.; ADEPOJU, A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Two feeding trials were carried out to examine the effect of graded dietary levels of protein and antibiotics on the performance of weanling local pigs. In the first trial, 5 groups of 12 pigs each, were fed a 16% protein diet containing respectively, 5 graded levels of strepcillin (0, 25, 50 75, 100g/tonne of diet). In the second trail, 9 groups of 8 pigs each, were fed 9 different diets respectively, in a 3 x 3 factorial arrangement of treatments (3 protein levels of 12, 15, 18%, 3 stepcillin levels of 0, 50, 75g/tonne). Daily gains, feed efficiency, scouring incidence, dry matter and crude protein digestibilities were recorded. Increasing dietary strepcillin improved (P <.05) growth rate and feed efficiency. The improvement plateaued at 75g strepcillin/tonne diet. A non-significant (P>.05) protein x antibiotics reduced scouring incidence, but had no significant effect on nutrient digestibilities.